Information management: axioms and theorems - Augustinaitis, Arūnas (Information & Media, 1996)
Education and research in information management (IM) were started at Vilnius University in 1991 together with the new Faculty of Communication. From the very outset of the branch they discussed the questions of conceptual development of IM, models and possibilities of its adaptation, in response to the traditions of information sciences and the experience of European countries and USA.They treat information management as a new paradigm of information activity. This paradigm corresponds to post-industrial tendencies. It is a relatively new branch with the very rapid development and its system of knowledge constantly changes and progresses. Due to this the understanding of IM is not monosemantic: it is under the effect of traditional information research influences, the development of communications and information technologies, the conceptions of modern management.This article is aimed to expose the main conceptual propositions that relatively are set in ("axioms") and those branches that raise complicated problems ("theorems"). The system of IM, the place of IM in academic context or the model of specialist could be mentioned among the latter ones.
Keywords: -